Safety and efficacy of DEB-TACE in combination with lenvatinib and camrelizumab for the treatment of unresectable hepatocellular carcinoma (uHCC): a two-centre retrospective study - Xuexian, Zhang; Ruidong, Wang; Yuhan, Ding; Qingwei, Li; Feng, Xiong; Hong, Ren; Jun, Zhang; Wei, Li (Frontiers in Immunology, 2024)
The purpose of this study was to compare the safety and efficacy of drug-eluting bead (DEB) transarterial chemoembolization combined with lenvatinib and camrelizumab (DEB-TACE-Len-C) and DEB-TACE-Len for the treatment of unresectable hepatocellular carcinoma (uHCC).Methods: This retrospective study consecutively included uHCC patients who underwent DEB-TACE-Len-C or DEB-TACE-Len treatment at our hospital and Qujing Second People's Hospital from April 2020 to April 2022. In total, 85 patients were enrolled. There were 42 patients in the DEB-TACE-Len-C group and 43 patients in the DEB-TACE-Len group. The disease control rate (DCR), objective response rate (ORR), overall survival (OS), progression-free survival (PFS), and adverse events (AEs) were compared between the two groups, and the factors influencing OS and PFS were analysed.